A case report A Nigerian adolescent with Long term Non-progressive HIV-infection: A case report - MM Ogundeyi; OO Oba-Daini; UP Adeniyi; BI Adenuga (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
Children infected with the Human Immunodeficiency Virus (HIV) can be rapid progressors or be at the end of the spectrum of the illness as Long-term Non-progressors (LTNPs). Long term non-progressors are patients who never received Highly Active Anti-Retroviral Therapy (HAART) during the first decade of life and are maintaining good CD4+ count associated with declining HIV RNA values. The literature on paediatric patients with LTNP infection is sparse. An adolescent with HIV LTNP and likely vertical transmission of HIV is presented in this report. She presented with chronic cough, severe anaemia and dyspnea. She was wasted with bodyweight less than the 5th centile for age. She was not sexually active and had no history of blood transfusion, scarification, incisions or sharing of sharp grooming objects. The results of investigations suggested pulmonary tuberculosis and HIV infection. Her CD4 count was 42%. She was commenced on HAART and subsequently, anti-tuberculosis medications according to NTBLCP/DOTS Programme with improvement in symptoms and appreciable weight gain. Therefore routine voluntary HIV testing is recommended for all paediatric admission after consent or assent is obtained bearing in mind that a small subset of patients may fall into the LTNPs population.